Persepsi Masyarakat Dalam Program Kota Tanpa Kumuh (KOTAKU) Di Kawasan Kelurahan Pahandut Kota Palangka Raya - Arifah Mir'atul Kusnah; Muhammad Riban Satia; Muhammad Nur Tanja Putra (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
This study aims to determine the Community Perceptions in the City without Slums Program (KotaKu) in the Pahandut Urban Area Palangkaraya City. The method used is qualitative. The researcher wants to describe the Community Perception in the City without Slums Program (KotaKu) in the Pahandut Urban Area of ​​Palangka Raya City by using 5 (five) performance indicators, namely Stimulation, Organization, Interpretation-evaluation, Memory, and Recall. The data source consisted of primary data, namely the results of interviews with 2 officials of the City Coordinator of the City of My City and the Acting Housing and Settlement Areas and 5 community members who received the KotaKu Program in the Pahandut Kelurahan, while the secondary data source was the SK Palangka Raya Mayor Document Number 188.45 / 130/2016 and Pahandut Village basline data. The results showed that the Community Perception in the City without Slums Program (KotaKu) in the Pahandut Kelurahan of Palangka Raya City that the facilities provided to the community could not be used optimally in accordance with their functions and lack of public awareness that the slum was a problem they had to solve itself, the government is only a tool to help provide the facilities they need for these problems. Cause this program is less than optimal even though the government has done its job well, because the impelamator of this program is the community itself. The program will be said to be successful if the facilities built can be used by the community. Suggestions from researchers provide regular outreach to the community, with the aim to change the community mindset that is the main problem of this program. Not only socialization, the government should continue to evaluate and remind that this function continues to work by the Working Group.